2022
DOI: 10.1002/nafm.10732
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of Juvenile Lake Sturgeon to Contaminants of Emerging Concern (CECs), Including Polybrominated Diphenyl Ethers (PBDEs): Location Differences and Effects on Thyroid Hormones

Abstract: Contaminants of emerging concern (CECs) are ubiquitous throughout aquatic environments. Previous research has shown that CECs can have detrimental effects on fish biology, potentially leading to population impacts. Specifically, polybrominated diphenyl ethers (PBDEs), a class of CECs, have been shown to alter thyroid hormones in fish, which can impact development, endocrine system functioning, and possibly imprinting. These impacts can lead to reproductive effects and population declines, which have serious im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This result differed slightly from similar data collected along the Maumee River (C. M. Custer et al, 2020) where no associations were detected between those or other biomarkers and PBDE exposure. These swallow results from the Milwaukee estuary, however, were similar to thyroid hormone work done on juvenile lake sturgeon in the Great Lakes, which also had only weak (T3, r 2 = 0.04) or nonsignificant (T4 in serum, p > 0.05) correlations with total PBDE concentrations (Hummel et al, 2022). Because of the large number of correlations ( n = 300) in the present study and the low r 2 value for PBDE associations, these associations from the Milwaukee estuary sites could be due to chance alone and should be viewed with caution without further corroborating evidence.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This result differed slightly from similar data collected along the Maumee River (C. M. Custer et al, 2020) where no associations were detected between those or other biomarkers and PBDE exposure. These swallow results from the Milwaukee estuary, however, were similar to thyroid hormone work done on juvenile lake sturgeon in the Great Lakes, which also had only weak (T3, r 2 = 0.04) or nonsignificant (T4 in serum, p > 0.05) correlations with total PBDE concentrations (Hummel et al, 2022). Because of the large number of correlations ( n = 300) in the present study and the low r 2 value for PBDE associations, these associations from the Milwaukee estuary sites could be due to chance alone and should be viewed with caution without further corroborating evidence.…”
Section: Discussionsupporting
confidence: 83%
“…Two, amphetamine and iopamidol, were detected in most liver tissues but were not detected in sediment. Iopamidol, however, was detected in two of three water samples collected at three lake sturgeon ( Acipenser fulvescens ) rearing facilities in the Milwaukee area (Hummel et al, 2022) but in only three of 13 sturgeon tissue samples. N,N ‐Diethyl‐meta‐toluamide was detected in all nestling samples including those from the reference lake.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, blood samples taken from lake sturgeon provided information about the occurrence and possible origins of select CECs that might contribute to understanding why sturgeon populations are struggling to recover in the Great Lakes (Banda et al, 2020). For example, studies on juvenile lake sturgeon from a streamside hatchery indicated that although exposure to CECs was occurring, this did not impact thyroid hormone titers enough to affect imprinting in the fish (Hummel et al, 2022). In other studies, collection of resident sunfish found a prevalence of adverse physiological effects at agriculturally dominated sites that would not necessarily have been predicted based solely on contaminant measurements (Cipoletti et al, 2020; Jorgenson et al, 2018; Thomas et al, 2017).…”
Section: Study Category 3: Occurrence Of Chemical Mixtures and Integr...mentioning
confidence: 99%